Resistance Training - Part I: Considerations in Maximizing Sport Performance - Plisk, S. (coachesinfo.com)
There is tremendous potential to improve an athlete's performance capability and minimize the risk of injury through specialized strength training. Principle-based planning and implementation of the preparation process is the key. This requires a working knowledge of physiological and biomechanical bases of maximum strength, speed-strength and strength-endurance development. In conclusion, the following practical implications can be recommended: Explosive force application is the basis of strength training for sports Functional strength is expressed in terms of acceleration, execution time or velocity - especially in athletics. Training tactics which disregard this fact are fundamentally unsound. Moving through an acceleration path, and applying rapid and/or high-speed force, is the name of the game. Emphasize big basic movements which have the greatest training effects; and use equipment which challenges the athlete to control, direct and/or stabilize it Muscles act in functional task groups, and must be targeted via force transmission through (rather than isolation within) the body's "kinetic chain". Multi-joint free weight movements are superior in this regard. Distinguish between specificity and simulation Training tasks should be selected and prioritized according to the coordinative, biomechanical and bioenergetic demands of competition. Balance the need for specificity vs. variability Maintain stability in the program by sticking with a basic exercise menu rather than trying to include every possible movement. Variation can be achieved by cycling workloads on a "periodic" 3-4 week basis in order to summate their training effects and avoid accommodation problems. Quality, not quantity, of effort is the bottom line While it is necessary to do enough work to get a training effect, there is likely a threshold of diminishing returns above which the athlete's effort is diluted - and recoverability / adaptability are compromised. Fitness and fatigue are a trade-off beyond a certain point. Generally, the best results are achieved by maximizing the quality of effort within a prescribed amount of work. Effort and recovery are interdependent The interrelation of workload, intensity, frequency and volume cannot be changed arbitrarily. They must be adjusted together, which occurs automatically with a sound plan. A training program is only as good as the athlete's ability to recover from and adapt to it! Fitness qualities are means toward an end, not ends in themselves: to develop the athlete's performance capabilities and skills, and thereby couple effort with execution Power, flexibility, agility, speed and endurance - combined with motor coordination - are the elements of athleticism. Each part can be trained, but they must be trained collectively because they are parts of a larger whole. None is a separate entity, nor more important than another. Train athletes, not muscles! Most importantly, skillful tasks are the basis of sports training, and require the services of a qualified Strength & Conditioning coach If simply counting reps and sets were the answer, anyone could do it. As is the case in all aspects of coaching or teaching, attention must be directed toward what the athlete is doing as well as how they are doing it - not just how much they do. Skilled training requires skilled coaching, and without it the program isn't worth the paper it's written on.